2003
DOI: 10.1002/gene.10175
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for novel fate of Flk1+ progenitor: Contribution to muscle lineage

Abstract: Flk1 is one of the specific cell surface receptors for vascular endothelial growth factor and one of the most specific markers highlighting the earliest stage of hematopoietic and vascular lineages. However, recent new evidence suggests that these Flk1(+) mesodermal progenitor cells also contribute to muscle lineages. All evidence is based on the experiments using in vitro differentiation and in vivo transplantation systems. Although this approach revealed a differentiation potential range of Flk1(+) cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
184
2
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(196 citation statements)
references
References 30 publications
7
184
2
3
Order By: Relevance
“…Blast colony-forming cells (BLCFCs) derived from EBs can generate hematopoietic and endothelial cell lineages, and represent the long-hypothesized hemangioblast (13,14). Flk1 ϩ cells may also give rise to smooth muscle cells (SMC) and cardiomyocytes under appropriate culture conditions (15)(16)(17).…”
Section: Embryonic Stem (Es)mentioning
confidence: 99%
See 1 more Smart Citation
“…Blast colony-forming cells (BLCFCs) derived from EBs can generate hematopoietic and endothelial cell lineages, and represent the long-hypothesized hemangioblast (13,14). Flk1 ϩ cells may also give rise to smooth muscle cells (SMC) and cardiomyocytes under appropriate culture conditions (15)(16)(17).…”
Section: Embryonic Stem (Es)mentioning
confidence: 99%
“…Blast colony-forming cells (BLCFCs) derived from EBs can generate hematopoietic and endothelial cell lineages, and represent the long-hypothesized hemangioblast (13,14). Flk1 ϩ cells may also give rise to smooth muscle cells (SMC) and cardiomyocytes under appropriate culture conditions (15)(16)(17).Wnts are paracrine/autocrine signaling molecules that have been implicated in many aspects of normal development. Canonical Wnt signaling acts through ␤-catenin and T-cell factor/lymphoid enhancer factor transcriptional factors that regulate target gene expression (reviewed in Refs.…”
mentioning
confidence: 99%
“…In the case of endothelial-specific gene targeting, several Cre lines have been developed with varying degrees of endothelial specificity (Gustafsson et al, 2001;Kisanuki et al, 2001;Motoike et al, 2003;Alva et al, 2006). Although extremely informative, the deletion of a wide array of genes using these lines has resulted in hemorrhage and eventual embryonic lethality.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, definitive hematopoietic stem cells are derived from a socalled hemogenic endothelium. Lineage tracing studies have shown that most leukocytes originate from cells expressing endothelial markers (found on blood vessel endothelial cells [BECs] during development and in the adult), including vascular endothelial growth factor receptor-2 (VEGFR-2), vascular endothelial cadherin (VE-Cadherin) or Tie-2/TEK (Motoike et al 2003;Chen et al 2009). Hence, a hematopoietic system cannot be established in the absence of a primitive endothelial system.…”
Section: The Interrelationship Of Lymphatic Endothelium and Hematopoimentioning
confidence: 99%